Project Design and Implementation of Electronic Archiving PT Multi Garmenjaya - Diva Puspa Mahardika (Ebiz Prima Nusa, 2024)
The interconnection of machines and humans to the Internet of Things (IoT), driven by trends in automation and data exchange with cyber-physical systems, will drive creativity and innovation in various fields. One area of particular interest is records administration which is moving away from conventional media and towards electronic storage and management. In this context, a literature study was conducted as a methodological approach. The purpose of this study was to gain insight into the potential of archive system design to provide a comprehensive framework for effective and systematic archive management. Records are stored in each section by dividing work groups, worksheet templates, worksheets, and designing fields for each worksheet. This makes it easier to store and search archives. From the explanation of the project report on the design of an electronic filing system at PT Multi Garmenjaya, it is found that the design of the filing system in this company using Image Ware Scan Manager provides convenience in archiving documents, thereby streamlining the company's operational activities. The existence of this archiving system design will at least provide an overview of good and organized archive management.